Sexual Socialization in Families with Adolescents (SSFA) in Thailand: Scale Development and Validation - Saranrittichai, Kesinee; Sakdisthanont, Supattana; Theeranut, Ampornpan; Jumparway, Donlagon; Sarakarn, Pongdech (Journal of Population and Social Studies [JPSS], 2020)
Although studies have shown the positive effects that families have on adolescent sexual health, there are still problems with clarification and validation of sexual socialization, and the process by which parents integrate adolescents into society to promote appropriate sexual learning and sexual health of adolescents. This cross-sectional study aimed to develop a valid and reliable Sexual Socialization in Families with Adolescents Scale (SSFAS) based on a qualitative framework. The participants were 460 parents with adolescents aged 13-19 years old studying in secondary and vocational schools. Stratified multi-stage random sampling was used. Item analysis was carried out using an exploratory factor analysis (EFA). A confirmatory factor analysis (CFA) was performed to confirm the components of the SSFAS. The results showed that the content validity index (CVI), Cronbach’s alpha coefficient, Kaiser-Meyer-Olkin measure of sampling adequacy, and Bartlett’s test of sphericity were appropriate. The five components of the SSFAS were: 1) General Pattern, 2) Trusting Pattern, 3) Strict Pattern, 4) Exhausted Pattern, and 5) Flexible Pattern. The eigenvalues of the five SSFAS components were greater than 1. The CFA statistics were fitted to the model. The findings suggested that the SSFAS can help identify sexual socialization patterns in families and screen the risk pattern of sexual socialization.